Mezőgazdasági ismeretek II rész
Town of Szabadkigyós. elderly man gives advice to other garden owners, summer activities in the fields, strawberry, rapsberry, spraying, irrigation, grapes, harvesting, storing, cattle, cucumber, autumn activities in the orchard